2012
DOI: 10.1088/0004-6256/143/6/138
|View full text |Cite
|
Sign up to set email alerts
|

Low Co Luminosities in Dwarf Galaxies

Abstract: We present maps of 12 CO J = 2 − 1 emission covering the entire star-forming disks of 16 nearby dwarf galaxies observed by the IRAM HERACLES survey. The data have 13 ′′ angular resolution, ∼ 250 pc at our average distance of D = 4 Mpc, and sample the galaxies by 10 − 1000 resolution elements. We apply stacking techniques to perform the first sensitive search for CO emission in dwarf galaxies outside the Local Group ranging from individual lines-of-sight, stacking over IR-bright regions of embedded star formati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
340
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(381 citation statements)
references
References 115 publications
38
340
3
Order By: Relevance
“…The black points show the molecular gas masses derived from the H 2 rotational model. The blue line shows a fit to this ratio derived from inverting the star formation law for HERACLES non-starburst galaxies (Schruba et al 2012). The molecular gas masses traced by the dust emission are denoted by the red points in the plot, and are shifted slightly in their metallicity values for clarity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The black points show the molecular gas masses derived from the H 2 rotational model. The blue line shows a fit to this ratio derived from inverting the star formation law for HERACLES non-starburst galaxies (Schruba et al 2012). The molecular gas masses traced by the dust emission are denoted by the red points in the plot, and are shifted slightly in their metallicity values for clarity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also shown that a CO in low-metallicity galaxies can be substantially higher than the Galactic value (e.g., Leroy et al 2011;Schruba et al 2012;Bolatto et al 2013) and hence we restricted our sample to galaxies with an oxygen abundance value of [ ]  + 12 log O H 8.4, using the average of their characteristic metallicities derived from a theoretical calibration and an empirical calibration as recommended by Moustakas et al (2010).…”
Section: Model-extrapolated Lower Temperature T ℓmentioning
confidence: 99%
See 2 more Smart Citations
“…Further studies have shown that indeed there is quite a bit of "CO-dark" molecular gas in these systems and other lowmetallicity regions in galaxies, and that they are not simply molecular gas-poor (e.g. McQuinn et al, 2012;Schruba et al, 2012;Blanc et al, 2013). The theoretical basis for this is that while H 2 can self-shield fairly easily, CO requires a column of dust approximately A V ∼ 1 to protect it from photo-dissociating radiation.…”
Section: Deriving H 2 Gas Masses From High-redshift Galaxiesmentioning
confidence: 95%